2011
DOI: 10.1007/s11104-011-0788-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant-induced changes in soil nutrient dynamics by native and invasive grass species

Abstract: Alteration of soil nutrient dynamics has recently garnered more attention as both a cause and an effect of plant invasion. This project examines how nutrient dynamics are affected by native (Elymus elymoides, Pseudoroegneria spicata, and Vulpia microstachys) and invasive (Aegilops triuncialis, Agropyron cristatum, Bromus tectorum, and Taeniatherum caput-medusae) grass species. This research questions whether natives and invasives differ in their effects on nutrient dynamics. A greenhouse study was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
3
33
1
1
Order By: Relevance
“…Additionally, our results indicate L microphyllum has a significant impact on the soil characteristics, and the effect is highly dependent on existing soil conditions. Impacts on the total nutrient pool and microbial community structure are con- cantly increased compared to the coexisting natives (Duda et al 2003;Vanderhoven, 2005;Dassonville et al 2008;Liao et al 2008;Perkins, 2011). This effect was most evident at sites with lowest nutrient con- Our results also show a difference in the rhizosphere microbial community which contributes directly to plant fitness, nutrient acquisition and stress tolerance.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, our results indicate L microphyllum has a significant impact on the soil characteristics, and the effect is highly dependent on existing soil conditions. Impacts on the total nutrient pool and microbial community structure are con- cantly increased compared to the coexisting natives (Duda et al 2003;Vanderhoven, 2005;Dassonville et al 2008;Liao et al 2008;Perkins, 2011). This effect was most evident at sites with lowest nutrient con- Our results also show a difference in the rhizosphere microbial community which contributes directly to plant fitness, nutrient acquisition and stress tolerance.…”
Section: Discussionmentioning
confidence: 61%
“…Most of the studies have reported increased soil nutrient stock in invaded sites compared to non-invaded sites creating a positive feedback benefiting invasive species (Duda et al2003;Vanderhoeven et al2005;Liao et al 2008;Perkins, 2011). A meta-analysis of litter decomposition rates by Liao et al (2008) showed that the litter decomposition rate of the invasive plants was on average, 117% faster than the co-occurring native species.…”
Section: Introductionmentioning
confidence: 99%
“…These results follow the general trend reported by various researchers, where the nutrient pools in the invasive species rhizosphere are significantly increased compared to the coexisting natives (Duda et al 2003;Vanderhoven 2005;Dassonville et al 2008;Liao et al 2008;Perkins 2011). This effect was most evident at sites with lowest nutrient concentration.…”
Section: Resultssupporting
confidence: 91%
“…However, the documented impacts of invasive species on soil characteristics are diverse. While most of the studies have reported increased soil nutrient stock in invaded sites compared to non-invaded sites creating a positive feedback benefiting invasive species (Duda et al 2003;Vanderhoeven et al 2005;Liao et al 2008;Perkins 2011), some other studies have shown negative feedback (Ley and D'Antonio 1998;Mack and D'Antonio 1998;Leary et al 2006). A meta-analysis of litter decomposition rates by Liao et al (2008) showed that the litter decomposition rate of the invasive plants was on average, 117% faster than the cooccurring native species.…”
Section: Introductionmentioning
confidence: 99%
“…Any of these changes could result in a legacy effect if soils remained biologically, physically, or chemically altered after its removal (Corbin and D'Antonio 2012). Other researchers have tested for invasive plant legacy effects by growing the invasive species in greenhouse soils for one or several growth cycles to condition the soil, removing the invader, and then comparing soil properties and/or growth of other plants in those same soils (Grman and Suding 2010;Scharfy et al 2010;Meisner et al 2011;Perkins et al 2011). Another method to test legacy effects is to compare plant growth in soils of known historical properties (Blank and Morgan 2013;Hagen et al 2013).…”
Section: Discussionmentioning
confidence: 99%